EVALUATIVE LANGUAGE FEATURES ON HOAX RELATED TO METH DRUGS IN DEALING WITH COVID 19 VIRUS - Situmeang, Anleny; Kurniawan, Muhammad Hafiz (Universitas Putera Batam, 2022)
Hoax news related to Covid 19 pandemic was spread in the US. In some cases, it is rather difficult to differentiate between real and fake news. Therefore, this study has an aim to analyse the evaluative features of online news using appraisal theory on the attitude subsystem. The appraising items focused on attitude division in the Huzlers about Corona Virus published in 2020 as the fake news and NBC news in 2012 as the real news regarding to the use of Meth to deal with Flu virus. Both news are American Media and were published online. This main purpose of this research is to explain the realization of fake and real news with the similar topics. The data used in this study was taken from Huzlers and NBC news and was collected in three steps: comparing, intensive reading, and transcribing. Moreover, the data were analysed into three steps: classifying, categorizing and analysing using Attitude theory which is one of appraisal theory aspects in SFL discourse semantics (Martin, J. R., & Rose 2007, Martin & White 2005, Martin 2019). The results of this study found that both news, real and fake news are dominated by appreciation. However, in fake news there is a tendency that the positive polarity is used to favour meth drugs, meanwhile in real news, it shows the polarity in balance. In addition, in fake news, there is also a tendency to use judgment to appraise the people involved in the meth drugs research.